Modelo animal de mania induzido pelo inibidor do transportador de dopamina GBR 12909: estudo de alterações comportamentais e neuroquímicas e prevenção/reversão pela minociclina - Queiroz, Ana Isabelle de Gois (2017)
Bipolar Disorder (BD) is a chronic and debilitating illness that affects around 2% of the world population. Even though it has a relatively high prevalence rate, its pharmacological treatment is still limited. This disorder is mainly characterized by the oscillation between phases of mania and depression, episodes which can only be mimicked in animal models separately once the cycling between them is a parameter that cannot yet be reproduced. This difficulty is due to the existence of restrictions to the mechanisms of action of the drugs used in BD animal models as well as to the subjectivity of this particular parameter. BD’s pathophysiology is characterized by oxidizing factors, alterations in neurotransmitters such as dopamine, and inflammatory activity, among others. Therefore, it is essential to have animal models that are able to mimic the clinical contexts of mania and depression as well as new substances that have activity in their pathophysiological pathways. The present study used a mouse model of mania induced by a dopamine transporter inhibitor (GBR12909) in order to investigate the behavioral, pharmacological and neurochemical alterations caused by the acute and sub-chronic administration of GBR12909 10mg / kg. These treatments aimed to mimic the pathophysiology of mania, thus being characterized as an animal model of mania. The study had 10 groups in which the animals were treated with either Minocycline (Mino), a tetracycline that presents clinical response in psychiatric disorders, at doses of 25 or 50mg / kg, Lithium (Li) 47.5mg / kg, Valproate (VAL) 200mg / kg or saline (control group). Based on the protocols followed during the research, experiments were divided into three chapters: (1) addressed the administration of GBR12909 as an animal model of mania, the temporal course of behavioral and oxidative alterations in specific brain areas, and the effects of mood stabilizing drugs, (2) focused on minocycline antimanic activity presented in the animal model of mania suggested and its possible role in antioxidant and neurotrophic mechanisms, (3) studied the influence of minocycline in behavioral changes (social interaction test, y-maze, plus-maze, social interaction) and pathophysiology through the evaluation of specific expression markers of intracellular hippocampal proteins (dopamine transporter - DAT and Iba, microglia marker) extracted from the animals submitted to the animal model of mania. Results indicated that GBR12909 caused alterations in locomotor activity 2h and 24h after its administration. Glutathione levels (GSH) decreased in the hippocampus and striatum at the time points of 2, 4, 8 and 12 h. An increase in lipid peroxidation was detected at the time points of 2 and 12 h in all brain areas studied. Li prevented alterations in horizontal and vertical hyperlocomotion 2h post-GBR12909, while VAL prevented vertical hyperlocomotion changes. Both drugs prevented pro-oxidative alterations. Subsequent evaluation of the prevention and reversal protocols showed that repeated administration of GBR12909 induced a hyperlocomotion increase, risk behavior, and memory, social interaction and cognition alterations. These changes were avoided by the administration of the mood stabilizers and both Mino doses. Hyperlocomotion and memory alterations were reversed by all drugs analyzed. Li, VAL or Mino were more effective in reversing GSH changes. As for lipid peroxidation, Mino was more effective in preventing and reversing its increase in the hippocampus whereas Li and VAL prevented it in the striatum and prefrontal cortex. Li, VAL and Mino25 reversed the decrease in BDNF levels induced by GBR12909. As for the quantification of DAT and IBA markers by immunoblotting, no expression of DAT was observed in any of the treated groups except saline. However, Li and Mino prevention groups showed a tendency of their IBA results going towards the same as of the control group, but without statistical significance. In conclusion, the administration of GBR12909 mimicked the manic phenotype, and Li, Val and Mino prevented and reversed manic-like behavior and acted in part on the neurochemical pathways of GBR12909-treated mice. Consequently, our data provides preclinical support for the design of trials investigating the possible antimanic effects of Mino in the GBR12909 induction model or other manic type animal models.